Analysis of Science Literacy Ability of Muhammadiyah Junior High School Students in Sidoarjo Based on Science Literacy Competencies - Syaifulloh, Mahyuddin; Hudha, Atok Miftachul; Inganah, Siti; Cholily, Yus Mochamad (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to identify the level of scientific literacy competencies among Muhammadiyah junior high school students in Sidoarjo, focusing on explaining scientific phenomena, interpreting scientific data and evidence, and evaluating and designing scientific investigations. A PISA-based scientific literacy test was administered to 275 students from eight schools. The results indicate that students’ overall scientific literacy competencies are in the low category, with an average score of 56.33%. Specifically, students demonstrate moderate ability in explaining scientific phenomena, while their abilities in interpreting data and evidence as well as evaluating and designing scientific investigations remain low. These findings reveal an imbalance across the dimensions of scientific literacy competencies within the Muhammadiyah school context. This study provides empirical evidence of specific weaknesses in students’ scientific literacy and highlights the urgent need to strengthen inquiry-based learning, problem-based learning, discovery learning, and the OIDDE learning model approaches to enhance students’ scientific reasoning skills at the junior high school level.